Strategic Directions of Pedagogical Personnel Training for the System of Continuing Vocational Education - E. F. Zeer; V. S. Tretyakova; V. I. Miroshnichenko (Образование и наука)
. Introduction. Transition to a post-industrial socio-economic structure and information society caused education crisis, which is common for world space. Dynamic development of high technologies and rapid obsolescence of knowledge significantly reduced life cycle of professions and caused deep structural changes in the sphere of employment. The need of economics for workers with qualitatively new qualification characteristics - a flexible person with meta-professional competencies, capable to solve complex professional problems and ready for innovative activity not just for today, but with the future in mind - has necessitated a significant updating of the system of vocational training and its reorganisation facilitating the implementation of a formula “lifelong learning”. The solution of problems of education begins with qualitative training of teachers, since the qualities of future professionals - graduates of the educational organisation, primarily depend on the level of teachers’ competencies.The aim of the present article is to determine the strategic directions of innovative development of vocational education and preparation of highly qualified pedagogical personnel.Methodology and research methods. The hypothetico-inductive method, theoretic-methodological analysis and synthesis of the content of scientific literature were the major research methods. The research work was carried out on the basis of the principle of convergence, which determines cross-disciplinary and supra-professional communications, acts as a factor of design and a statement in professiology of a new phenomenon - transprofessionalism. The authors described the concept of transprofessionalism through the process- and project-based approaches.Results and scientific novelty. The developmental trends and directions of vocational education are considered. The principal defining factor of vocational education is close integration of all its processes and subsystems (prevocational training - secondary vocational education - higher education institutions - postgraduate training), which integrity is provided by the continuing and advanced education. The concept of transprofessionalism and convergence in multidisciplinary training of specialists is proved. The innovative educational programmes based on this concept are characterised. The logical-semantic model of a modern specialist is designed. This model can form an empirical basis to design vocational education platform, which integrates socio-humanistic, natural-science disciplines and related innovative technologies for teachers’ training in the system of continuing vocational education. Strategic directions for realisation of such preparation are formulated: transprofessionalism, cooperation / collaboration, advanced and “high-speed” training, digital transformation.Practical significance. The research materials can be useful for specialists in the field of vocational education, heads of the educational organisations in order to develop and make managerial decisions and to effectively organise the process of vocational training of pedagogical personnel.